Analysing how crises shape mass and elite preferences and behaviour in the European Union. (March 2022) - De Vries, Catherine E
The COVID-19 pandemic proved the latest stress test for the European Union, after Brexit, the Eurozone crisis and the large influx of refugees. This highly relevant and well-timed special issue examines how past crises have left an imprint on the opinions and behaviour of ordinary citizens and political elites regarding the European Union. This Forum article reviews the special issue contributions by spelling out which lessons we can learn from each of them and which paths for future research they have opened up. In terms of a path forward, I argue that scholars ought to pay more attention to (a) the role of political elites, (b) political opportunity structures, and (c) heterogeneity both between and within member states.